Peningkatan Kualitas Pendidikan di Pesantren Melalui Inovasi Kurikulum - Rahmad Fuad; Iswantir M (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Islamic boarding schools often face various challenges that make it difficult for them to keep up with the times, sometimes even considered less creative. Some pesantren are still rigid in maintaining the salafiyah pattern that they consider old-fashioned in dealing with external issues. In fact, as an educational, religious, and social institution, pesantren need to innovate without losing their basic values. The author observes a renewal in Islamic education, especially in Islamic boarding schools, by incorporating sciences such as natural sciences, social sciences, and other general knowledge into the curriculum. Therefore, this research uses qualitative research methods with data collection techniques in the form of observation, interviews, and documentation. The results showed that there are two types of education in pesantren, namely pesantren education and general education. Both types of education provide knowledge to students to deal with diverse social life, especially in terms of moral education that is not taught formally in public schools. With these two types of education, students can also adapt to the development of science and technology, so they are ready to face challenges in this modern era.